ANALISIS EFEKTIVITAS LAYANAN KONSELING INDIVIDUAL DALAM REHABILITASI KLIEN KECANDUAN NARKOBA - Miftahul Rahmah; Imam Rifai; fadila; Syamsul Rizal (STKIP Subang, 2026)
In an effort to address the problem of drug addiction, individual counseling services play a very important role. This service enables counselors to provide direct, face-to-face, and personalized assistance to clients, thereby creating a deep and trusting relationship (rapport). Individual counseling aims to help clients understand themselves, identify their problems, and develop self-regulation and self-control skills in order to overcome addiction and prevent relapse. This journal employs a literature study approach. The findings indicate that individual counseling plays a crucial role in the recovery process of drug addiction. Through a personal and structured approach, this counseling helps build a trusting relationship between the counselor and the client, allowing the client to feel comfortable opening up and addressing their addiction-related problems. The counseling process includes stages of assessment, problem identification, therapy, evaluation, and commitment reinforcement, all of which are designed to support changes in negative behaviors and thought patterns. The factors causing narcotics addiction are highly complex, involving internal aspects such as personality, psychological conditions, and family environment, as well as external factors such as social influences and the easy accessibility of drugs. Therefore, effective individual counseling must be able to accommodate these various factors in a holistic manner. Individual counseling services have been proven effective in the rehabilitation process of clients with drug addiction. Through a personal approach, emotional support, identification of underlying problems, development of coping skills, and periodic monitoring, individual counseling provides a strong foundation for clients to achieve sustainable recovery.